Comparing the competition of Malaysia Islamic and conventional banks: Evidence surrounding the global financial crisis - Wahid M.A. (Emerald Group Publishing Ltd., 2024)
Purpose: This study aims to analyse three main questions within the Malaysian banking system: Are Islamic banks more competitive than conventional banks? What are the levels of competition for Islamic and conventional banking sectors pre, during and post the 2007-2009 global financial crisis? Does penetration of Islamic banks affect the competitive structure of conventional banks? Design/methodology/approach: In measuring a bank competition, the author estimates the PanzarRosse H-statistic (PRH) method on 17 Islamic and 21 conventional banks in Malaysia over the period of 2004-2013. This is then followed by ordinary least squares (OLS) robust regression analysis to control Islamic banks penetration, bank-specific and macroeconomic factors. Findings: Results from the PRH method (total revenue) suggest that Malaysian Islamic banks are relatively more competitive than their conventional counterparts. Furthermore, the author observes that the level of competition for both Malaysian Islamic and conventional banks increased tremendously during the 2007-2009 global financial crisis. This suggests the impact of the crisis on the level of competition for both banking systems. Finally, the OLS robust regression suggests that Islamic banks penetration has a significantly positive impact on the level of competition for conventional banks. The PRH estimation using total interest income indicates similar results, suggesting the robustness of these results. Practical implications: This study reveals whether Islamic banks penetration is able to increase the level of competition within the conventional banking sector. Knowledge on this is important to the policymaker. Originality/value: To the best of the authors knowledge, this is the first study using the PRH method in comparing the level of competition for Malaysian Islamic and conventional banks. Furthermore, this is the first study analysing the impact of Malaysian Islamic banks penetration on the level of competition for conventional banks. 2017, Emerald Publishing Limited.